Cloud Computing: Architecture for Efficient Provision of Services - Khan, Nawsher; Noraziah, Ahmad; Tutut, Herawan; Elrasheed, Ismail (Conference Publishing Services (CPS), 2012)
Reliability, efficiency (in term of time consumption) and effectiveness in resources utilization are the desired quality attributes of Cloud Scheduling System, the main purpose of which is to execute jobs optimally, i.e. with minimum average waiting, turnaround and response time. Replication provides improved availability, decreased bandwidth use, increased fault tolerance, and improved scalability. To speed up access, file can be replicated so a user can access a nearby replica. In this paper, we propose architecture to convert Globally One Cloud to Locally Many Clouds. By combining replication and scheduling, this architecture will improve efficiency, accessibility and reliability. In the case of failure of one sub cloud or one cloud service, clients can start using another cloud under “failover” techniques. As a result, no one cloud service will go down.